A study on the impacts of service quality and relationship quality on customer satisfaction at a Celcom outlet in Kemaman / Fatin Amirah Azhar - Azhar, Fatin Amirah (2015)
The purpose of this study is to investigate the impact of service quality and relationship quality on customer satisfaction at a Celcom Outlet in Kemaman. The research was conducted based on nine hyphothesis that relate to the elements of independent variables that is service quality and relationship quality with dependent variables that is customer satisfaction. This research uses correlation and regression analysis to investigate the impact of service quality and relationship quality on customer satisfaction. In conducting this research, the instrument of data collection method used in this research was a questionnaire which has been adapted from previous studies and the data was analyzed usisng the Statistical Package in the Social Science Software (SPSS) version 20. In this study, the unit of analysis are the individual customer of Celcom Outlet in Kemaman. The findings of the study showed that service quality and relationship quality positively affect customer satisfaction. The results also revealed that, among the five elements of service quality, only reliability and responsiveness significantly influnce customer satisfaction. Both elements of relationship quality, customer trust and customer commitment significantly positive effect on customer satisfaction. The conclusion and suggestions for future research were made as to develop better understanding on the impact of both service elements on customer satisfaction.